Applying Standard Clinical Chemistry Assay Validation to Droplet Digital PCR Quantitative Liquid Biopsy Testing. (4th January 2020) - Milosevic, Dragana; Mills, John R; Campion, Michael B; Vidal-Folch, Noemi; Voss, Jesse S; Halling, Kevin C; Highsmith, W Edward; Liu, Minetta C; Kipp, Benjamin R; Grebe, Stefan K G
Abstract: BACKGROUND: Droplet digital PCR (ddPCR) is an emerging technology for quantitative cell-free DNA oncology applications. However, assay performance criteria must be established in a standardized manner to harness this potential. We reasoned that standard protocols used in clinical chemistry assay validation should be able to fill this need. METHODS: We validated KRAS, EGFR, and BRAF quantitative ddPCR assays based on the Clinical Laboratory Improvement Act regulations for laboratory-developed tests in clinical chemistry and the matching Clinical and Laboratory Standards Institute guidelines. This included evaluation of limit of the blank (LOB), limit of detection (LOD), limit of quantification (LOQ), intraassay and interassay imprecision, analytical range, dilution linearity, accuracy (including comparison with orthogonal platforms), reference range study, interference, and stability studies. RESULTS: For the ddPCR assays, the LOB was 4 mutant copies, LODs were 12 to 22 copies, and LOQs were 35 to 64 copies. The upper limit of the dynamic range was 30000 copies, and dilutions were linear down to the LOQs with good accuracy of spike recovery of Horizon reference material. Method comparisons with next-generation sequencing and an alternative ddPCR platform showed complete qualitative agreement and quantitative concordance, with slopes of 0.73 to 0.97 and R 2 s of 0.83 to 0.99. No substantial interferences were discovered. Wild-type copy numbers in plasma ranged from 462 to 6169/mL in healthy individuals. CONCLUSIONS: Standard clinical chemistry assay validation protocols can be applied to quantitative ddPCR assays. This should facilitate comparison of the performance of different assays and allow establishment of minimal significant change thresholds in monitoring applications.